Thermal Paper
The coated paper article with a base coat layer of porous multistage polymer particles addresses the challenge of predicting printing performance in thermal papers, achieving enhanced printing efficiency through controlled porosity and shell composition.
Patent Information
- Application Number
- JP2024533296
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-20
- Filing Date
- 2022-12-06
- Publication Date
- 2024-12-13
AI Technical Summary
Existing thermal papers face challenges in achieving improved printing performance due to the limitations of porosity in hollow sphere pigments, which do not adequately predict printing energy requirements.
A coated paper article is developed with a base coat layer comprising porous multistage polymer particles having a shell-hollow core morphology, a specific particle size, and a shell composition of styrene and carboxylic acid monomer salts, with a controlled pore area between 0.005% to 0.5% of the surface area, enhancing printing performance.
The solution results in thermal paper with improved printing performance by reducing the energy required for image generation, as demonstrated by increased optical density at lower printing energies.
Smart Images

Figure 2024545869000001 
Figure 2024545869000002 
Figure 2024545869000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermal paper having a base coat containing porous hollow sphere pigments, particularly porous hollow sphere pigments having a high porosity.
[0002] Thermal paper is a multi-layer recording material that includes a paper substrate, an intermediate heat insulating layer containing hollow sphere pigment (HSP), and an image forming layer (see U.S. Pat. No. 10,730,334(B1)). Print performance in direct thermal printing applications is highly dependent on maximizing the porosity of the HSP. The greater the porosity, the less printing energy is required to generate and image. However, porosity alone cannot predict print performance. Therefore, it would be advantageous in the field of thermal printing to provide an HSP that results in improved print performance. Summary of the Invention
[0003] The present invention relates to a coated paper article comprising: a) a paper base material having a thickness of 40 μm to 500 μm; b) a base coat layer having a thickness of 2 μm to 10 μm, the base coat layer comprising porous multi-stage polymer particles and a binder; c) a thermal recording layer having a thickness of 1 μm to 30 μm; The base coat layer is disposed between the thermal recording layer and the paper substrate, the porous multi-stage polymer particles have a shell-hollow core morphology and a number weighted average particle size in the range of 500 nm to 3 μm; the shell comprises 0.5 to 10 weight percent structural units of a salt of a carboxylic acid monomer and 90 to 99.5 weight percent structural units of styrene; at least 98 weight percent of the shell comprises structural units of a salt of styrene and a carboxylic acid monomer; The need in the art is addressed by providing a coated paper article having a percent pore area in the range of 0.005 to 0.5 percent of the surface area of the multi-stage polymer particles.
[0004] The article of the present invention provides thermal paper with improved printing performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0005] The present invention relates to a coated paper article comprising: a) a paper base material having a thickness of 40 μm to 500 μm; b) a base coat layer having a thickness of 2 μm to 10 μm, the base coat layer comprising porous multi-stage polymer particles and a binder; c) a thermal recording layer having a thickness of 1 μm to 30 μm; The base coat layer is disposed between the thermal recording layer and the paper substrate, the porous multi-stage polymer particles have a shell-hollow core morphology and a number weighted average particle size in the range of 500 nm to 3 μm; the shell comprises 0.5 to 10 weight percent structural units of a salt of a carboxylic acid monomer and 90 to 99.5 weight percent structural units of styrene; at least 98 weight percent of the shell comprises structural units of a salt of styrene and a carboxylic acid monomer; The coated paper article has a percent pore area in the range of 0.005 to 0.5 percent of the surface area of the multi-stage polymer particles.
[0006] The basecoat layer comprises a binder and multi-stage polymer particles having a) hollow core-shell morphology (HSP) and b) pores that are channels extending from the surface of the particle to the hollow core. The porous HSP is advantageously prepared as follows: A dispersion of first stage polymer particles is prepared by reacting methyl methacrylate with methyl acrylate under aqueous emulsion polymerization conditions to form an aqueous dispersion of first stage polymer particles having a z-average particle size, as measured by dynamic light scattering, ranging from 200 or 300 nm to 750 or 600 nm. The dispersion of first stage polymer particles is then reacted under aqueous emulsion polymerization conditions with styrene and carboxylic acid monomers to form an aqueous dispersion of solid polymer particles comprising a first stage having methyl acrylate and methyl methacrylate structural units and a second stage (i.e., shell) having structural units of styrene and carboxylic acid monomers.
[0007] Examples of carboxylic acid monomers include acrylic acid, methacrylic acid, and itaconic acid, with acrylic acid being preferred. At least 98, or at least 99, or at least 99.5 weight percent of the second stage comprises structural units of styrene and carboxylic acid monomers or salts thereof. Preferably, the second stage comprises less than 1 weight percent, or less than 0.5 weight percent, or less than 0.1 weight percent, or 0 weight percent of any C1-C 20 Alkyl acrylate or methacrylate or any C3-C 20 The weight to weight ratio of monomers used to prepare the second stage to monomers used to prepare the first stage (i.e., stage 2:stage 1 ratio) is preferably in the range of 5:1 or 7:1 or 8:1 to 12:1 or 10:1 or 9:1.
[0008] The aqueous dispersion of non-porous multi-stage polymer particles is then converted to an aqueous dispersion of multi-stage porous polymer particles under conditions sufficient to hydrolyze the methyl acrylate to acrylic acid or a salt thereof. Hydrolysis can be carried out, for example, by contacting the dispersion of non-porous polymer particles with NaOH at elevated pressure at a temperature ranging from 100° C. to 150° C. Hydrolysis produces swollen porous core-shell polymer particles, where the first stage polymer core comprises water and structural units of methyl methacrylate and sodium acrylate, and the second stage polymer shell comprises at least 98 weight percent structural units of styrene and salts of carboxylic acid monomers. The core becomes hollow upon evaporation of the water. The average diameter particle size of the swollen porous multi-stage polymer particles ranges from 500 nm, or from 750 nm, or from 900 nm to 3 μm, or from 2 μm, or from 1.8 μm, or from 1.5 μm, or from 1.2 μm.
[0009] The percent pore area ranges from 0.005 percent, or from 0.01 percent to 0.5 percent, or to 0.2 percent, or to 0.1 percent, or to 0.06 percent of the area of the multi-stage polymer particle. The porosity of the porous HSP typically ranges from 60% to 75%, or to 70%, or to 65%.
[0010] Thermal recording materials typically contain a leuco dye and a color developer (see U.S. Pat. No. 4,929,590), and may contain various other additives, including binders, fillers, crosslinking agents, surfactants, sensitizers, and heat-fusible materials. Thermal papers can be prepared by methods known in the art, such as those described in the Examples section. EXAMPLES
[0011] Determination of Percent Porosity Particle porosity is determined using the following procedure: Add the latex (40 g) containing the porous polymer to a 50 mL polypropylene centrifuge tube (with a hemispherical bottom). Place the tube in a centrifuge and spin at 18,500 rpm for 120 minutes. Decant the clear supernatant from the hard pack and weigh. From the latex mass, percent solids, and supernatant mass, determine the percent void fraction (VF%) using the following formula:
[0012]
number
[0013] Particle size measurement The size of the hollow spherical particles was measured based on scanning electron micrographs (SEM). Two drops of the emulsion were drop-cast onto a conductive carbon tape on an aluminum SEM tab. After drying for 2 h at ambient temperature, the samples were coated with a thin layer of chromium in an EMS 150T ES metal coater using a sputter current of 100 mA for 100 s. SEM was acquired at 5 kV accelerating voltage from a Schottky field emission electron source using an Everhart-Thornley secondary electron detector in a Thermo Fisher Nova NanoSEM 630 scanning electron microscope. All images were acquired at a magnification of 20,000× with an image size of 1024 × 884 pixels and a bit depth of 8 (grayscale ranged from 0 to 255, where 0 is the darkest and 255 is the brightest). All images had a horizontal field of view of 7.46 μm and a pixel size of 7.28 nm. Each image contained 40-60 hollow sphere particles. Two images were analyzed for each sample using ImageJ software (version 1.53c). Diameters were measured manually for all particles in the image, excluding particles at the edge of the image. Number-weighted mean particle size and standard deviation were reported.
[0014] Pore area percent determination The pore area percent was measured using the same SEM used to measure particle size. Two images were analyzed for each sample using ImageJ software (version 1.53c). All images were preprocessed using the "Smooth" command in ImageJ followed by the "Contrast Enhance" command at 0.3% saturated pixels and with the "Normalize" option enabled. Pores appeared in the micrographs as dark areas on the bright particle surface. A grayscale value of 60 was used as the segmentation threshold to isolate pores for area measurements. Bright pixels with grayscale values between 61 and 255 constituted particles and their total area was defined as A. 粒子The area of the selected pores was recorded as A. Dark pixels with a grayscale value between 0 and 60 constituted either pores or interstitial sites (dark regions between particles). To distinguish between pores and interstitial sites, two additional constraints were used: the size of the pores was between 9 and 800 pixels, and the circularity was between 0.70 and 1.00. Using these criteria, any interstitial sites that were incorrectly selected by the software were manually excluded from selection. After these adjustments, the total area of selected pores was defined as A. 細孔 The percent pore area was then defined by the following formula:
[0015]
number
[0016] Intermediate Example 1 - Preparation of an Aqueous Dispersion of Porous Hollow Spherical Polymer Particles A. Preparation of the First Stage Polymer Dispersion Deionized water (1630.00 g) and glacial acetic acid (0.50 g) were charged to a 5 L, 4-neck round bottom flask and heated to 92° C. under N2. In a separate vessel, a monomer emulsion was prepared containing deionized water (335.33 g), sodium dodecylbenzenesulfonate (30.22 g, 22.5% in water), methyl methacrylate (940.40 g), and methyl acrylate (681.00 g). An initiator solution of sodium persulfate (3.02 g) in deionized water (90 g) and a buffer solution of sodium bicarbonate (0.27 g) in deionized water (90 g) were also prepared. A solution of sodium persulfate (1.51 g) in deionized water (20 g) was charged to the reactor and rinsed with deionized water (10 g). The acrylic seed polymer dispersion (55.39 g, 45.6% solids, 100 nm) was charged to the reactor and rinsed with deionized water (10 g). The monomer emulsion, initiator solution, and buffer solution were then fed into the reactor over 180 minutes while the reaction was held at 90° C. Once the feeds were complete, the vessel was rinsed with deionized water (50 g total) and the reaction was held at 90° C. for 15 minutes before being cooled to room temperature. The resulting core polymer dispersion had a solids content of 41.7 wt %.
[0017] B. Preparation of Dispersions of Non-Porous Multi-Stage Polymer Particles Deionized water (1668.00 g) and glacial acetic acid (0.50 g) were charged to a 5 L, 4-neck round bottom flask and heated to 95° C. under N2. In a separate vessel, a monomer emulsion was prepared containing deionized water (112.30 g), sodium dodecylbenzenesulfonate (3.15 g, 22.5% in water), styrene (712.73 g), and acrylic acid (29.37 g). A solution of sodium persulfate (2.18 g) in deionized water (20 g) was charged to the reactor and rinsed with water (5 g). A portion of the first stage polymer dispersion from Part A (231.24 g) was charged to the reactor and rinsed with deionized water (20 g). The monomer emulsion was fed to the reactor over 100 minutes while the reaction was maintained at 90° C. Once the monomer emulsion feed was complete, the monomer emulsion vessel was rinsed with deionized water (40 g) and the reaction was held at 90° C. for 45 minutes before being cooled to room temperature. The resulting dispersion of non-porous multistage polymer particles had a solids content of 28.8 wt %.
[0018] C. Preparation of Aqueous Dispersions of Porous Polymer Particles A portion of Intermediate 1B (205.9 g) was mixed with deionized water (95.8 g) and sodium hydroxide solution (5% in water, 49.5 g). The resulting dispersion was charged to a pressure vessel and heated to 140° C. After 6 hours, the vessel was cooled to room temperature and the swollen porous particle dispersion was removed. The dispersion of porous polymer particles had a final pH of 11.5, a solids content of 17.8 wt. %, and a pH of 1.03. + It had a number weighted particle size of 0.06 μm, a porosity of 61.7%, and a pore area percentage of 0.03 area percent.
[0019] Intermediate Example 2 - Preparation of Basecoat Formulation A portion of Intermediate Example 1C (67.4 g), RHOPLEX™ P-308 styrene-acrylic binder (P-308, 4.5 g, 50 wt % solids, a trademark of The Dow Chemical Company or its affiliates), and #67710 polyvinyl alcohol (PVOH, 5 g, 15 wt % in demineralized water, Kremer Pigmente) were mixed in a vessel equipped with an overhead blade mixer and then diluted with deionized water (23.1 g) to adjust to 17 wt % solids.
[0020] Comparative Intermediate Example 1 - Preparation of Aqueous Dispersions of Porous Polymer Particles The procedure of Intermediate Example 1 was substantially repeated, except that the non-porous multi-stage dispersion was prepared using styrene (696.50 g), methyl acrylate (37.10 g), and acrylic acid (8.50 g). The resulting dispersion was found to have a solids content of 29.0 wt.%. A porous dispersion was prepared by reacting a portion of the non-porous multi-stage dispersion (203.9 g) with deionized water (80.40 g) and sodium hydroxide solution (68.2 g, 5 wt. % in water). The dispersion of porous polymer particles had a final pH of 12.7, a solids content of 18.4 wt.%, and a pH of 0.98. + It had a number weighted particle size of 0.07 μm, a porosity of 63.2%, and a percent pore area of 1.06 area percent.
[0021] Comparative Intermediate Example 2 - Preparation of an Aqueous Dispersion of Porous Polymer Particles The procedure of Intermediate Example 1 was substantially repeated, except that the non-porous multi-stage dispersion was prepared using styrene (659.40 g), methyl acrylate (74.20 g), and acrylic acid (8.50 g). The resulting dispersion was found to have a solids content of 28.3% by weight. A porous dispersion was prepared by reacting a portion of the non-porous dispersion (209.4 g) with deionized water (55.48 g) and sodium hydroxide solution (97.3 g, 5% by weight in water). The dispersion of porous polymer particles had a final pH of 13.0, a solids content of 18.4% by weight, and a pH of 0.93. +It had a number weighted particle size of 0.06 μm, a porosity of 62.6%, and a percent pore area of 1.71 area percent.
[0022] Comparative Intermediate Example 3 - Preparation of Basecoat Formulation A portion of the aqueous dispersion of porous polymer particles from Comparative Intermediate Example 1 (67.2 g), P-308 (4.5 g), and PVOH (5 g) were mixed in a vessel equipped with an overhead blade mixer and then diluted with deionized water (23.4 g) to an adjusted solids content of 17% by weight.
[0023] Comparative Intermediate Example 4 - Preparation of Basecoat Formulation A portion of the aqueous dispersion of porous hollow spherical particles from Comparative Intermediate Example 2 (66.2 g), P-308 (4.5 g), and PVOH (5 g) were mixed in a vessel equipped with an overhead blade mixer and then diluted with deionized water (24.3 g) to an adjusted solids content of 17% by weight.
[0024] Intermediate Example 3 - Thermosensitive Recording Layer Formulation Materials and formulations were obtained from Nissho Kogyo Co, LTD. Deionized water (51.6 g) was placed in an 8 ounce container, followed by the addition, in order, of Tunex-E precipitated calcium carbonate (4.4 g), P-603 Mizucasil silicon dioxide (3.7 g), PVA-203 buffer (1.0 g, Kuraray 15 wt%), D-8 4-hydroxy-4'-isopropoxydiphenylsulfone developer (8.8 g, Mitsubishi, 50 wt%), 2-benzyl-oxy-naphthalene sensitizer (4.0 g, 40 wt%), PVA-117 binder (15.8 g, Kuraray, 10 wt%), zinc stearate lubricant (3.1 g, 36 wt%), and PSD-290 2-anilino-6-(dibutylamino)-3-methylfluoran dye (5.7 g, Mitsubishi, 35 wt%) and mixed with an overhead blade mixer.
[0025] Examples 1 and Comparative Examples 2 and 3-Preparation of Coated Paper with Image Layer NewPage Free Sheet Paper (grammage: 58g / m 2 A sheet of 1000 mm thick paper (1000 mm thick, roughness: 4.00 μm, Gurley porosity: 24.6 s) was cut to 37.9 cm by 20.1 cm with the long edge in the machine direction and then placed in a controlled temperature room (72° F. (22° C.), 50% humidity) for at least 2 hours. Using masking tape, the paper was taped to a piece of copy paper, which was attached to a hand drawdown plate with the masking tape. A bead of basecoat formulation was then pipetted onto the masking tape on the free sheet. A wire-wrapped rod was then manually lowered onto the strip of basecoat formulation and moved across the paper so that the paper was evenly coated. The paper was then exposed to hot air for 45 seconds, after which the paper was transferred to an oven and dried at 80° C. for an additional 45 seconds. After drying, the paper was conditioned in a controlled temperature room (72° F. and 50% humidity) for 2 hours. This paper with the base coat was then coated with an image layer using the same procedure used to apply the base coat and dried at 80° C. for 1 minute.
[0026] Dynamic Sensitivity Measurement The fully coated paper was cut in the machine direction into two strips 2.5 inches (1 cm) wide. The two strips were taped end to end and printed using an Atlantek Paper Tester Model 200 and used to measure dynamic sensitivity using the following printing conditions:
[0027] a) Sequence dot pulse duration = 0.8ms b) Full cycle time (T cycle )=5.0ms c) Print head temperature = 30°C d) Printhead resistance = 583 Ohms at an applied voltage of 20.6V
[0028] A 50% 80x80 checkerboard pattern was printed at print energies of 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, and 0.50 mJ / dot. The optical density of three boxes was measured for each print energy using a handheld X-rite 428 spectrodensitometer.
[0029] The optical density of the coated paper of Example 1 was found to be 0.59 at a print energy of 0.2 mJ. In contrast, the optical density of the coated papers of Comparative Examples 1 and 2 was found to be 0.49 and 0.41, respectively, at the same print energy. The porous HSPs had similar porosity (61.7% to 63.1%). Nevertheless, the base coat containing the HSP with a significantly smaller pore area percentage resulted in a coated paper with increased optical density at a given print energy.
Claims
1. 1. A coated paper article comprising: a) a paper substrate having a thickness of 40 μm to 500 μm; b) a 2 μm to 10 μm thick basecoat layer comprising porous multi-stage polymer particles and a binder; c) a thermal recording layer having a thickness of 1 μm to 30 μm; the base coat layer is disposed between the thermal recording layer and the paper substrate; said porous multi-stage polymer particles having a shell-hollow core morphology and a number weighted average particle size ranging from 500 nm to 3 μm; the shell comprises 0.5 to 10 weight percent structural units of a salt of a carboxylic acid monomer and 90 to 99.5 weight percent structural units of styrene; at least 98 weight percent of said shell comprises structural units of styrene and said salt of said carboxylic acid monomer; A coated paper article having a percent pore area in the range of 0.005 to 0.5 percent of the surface area of said multi-stage polymer particles.
2. 2. The coated paper article of claim 1, wherein at least 99 weight percent of the shell of the multi-stage polymer particles comprises structural units of styrene and a carboxylic acid monomer, the carboxylic acid monomer being acrylic acid or a salt thereof or methacrylic acid or a salt thereof.
3. The shell of the porous multi-stage polymer particles is less than 0.5 weight percent of any C 1 ~C 20 The coated paper article of claim 1 comprising structural units of an alkyl acrylate or methacrylate.
4. The shell of the porous multi-stage polymer particles is less than 0.5 weight percent of any C 3 ~C 20 10. The coated paper article of claim 1 comprising structural units of a cycloalkyl acrylate or methacrylate.
5. The coated paper article of claim 2, wherein the number weighted average particle size of the porous multi-stage polymer particles is in the range of 750 nm to 1.5 μm.
6. 6. The coated paper article of claim 5, wherein the average area percent is in the range of 0.01 to 0.1 percent of the surface area of said porous multi-stage polymer particles, and said number weighted average particle size of said porous multi-stage polymer particles is in the range of 900 nm to 1.2 μm.
7. The coated paper article of claim 6, wherein said porous multi-stage polymer particles have a porosity in the range of 60% to 75%.
8. The coated paper article of claim 6, wherein said porous multi-stage polymer particles have a porosity in the range of 60% to 70%.
